Traveling wave based fault location for power transmission lines using morphological filters and clarke modal components - Elmahdi Khoudry; Abdelaziz Belfqih; Jamal Boukherouaa; Faissal Elmariami (International Journal of Electrical and Computer Engineering (IJECE), 2020)
This article presents a fast and accurate fault location approach for power transmission lines based on the theory of traveling waves. In fact, when faults occur, they give rise to transient voltages and currents that propagate at a speed close to that of light along the transmission line as traveling waves. Moreover, according to the superposition theorem, each of these transients is a combination of a steady-state quantity and an incremental quantity. These transient signals measured at both ends of the line are first transformed to the Clarke (0-α-β components) components in order to categorize the type of faults, and then multi-scale morphological gradient filters are used to extract equivalent quantities to the incremental quantities to form what are called characteristic signals. These latter will be used to identify the fault location according to the proposed algorithm.